ANALISIS PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Sri Hardianti; Zulkarnain Zulkarnain (Universitas Pahlawan, 2019)
This study was conducted in Tarai Bangun, Kualu and Teluk Kenidai Tambang District, Kampar. The objective of this research was to analyze the influence of age, education, employment, infrastructure, knowledge and attitudes on public participation in household waste management in the area. Method used in this research was quantitative analytic cross sectional. Study showed that age (0.583), education (0.749), employment (0.988), and attitudes (0.081) significantly did not affect public participation in household waste management. However, infrastructure (0.023) and knowledge (0.043) has significant influence on public participation. Of the two aforementioned variables, knowledge is the most dominant factor, that is ; 3.401 times. Public participation in household waste management in three villages in Tambang district, Kampar is concluded poor due to low public awareness on environmental cleanliness.